Analisa Sistem Manajemen Perawatan Pompa Roda Gigi Di Kapal KM. Kelimutu - Haryadi, Sugeng; Hermawati, Lilin; Pratomo, Sunu Arsy (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
This study focuses on the management of gear pump maintenance on KM Kelimutu ship. Data collection methods are used to identify and investigate the causes of damage that occur in the gear pump. The required maintenance and repair actions are determined based on the analysis results. The process of managing maintenance involves several important steps. First, planning is carried out to determine the planned maintenance actions. Subsequently, organization is conducted by appointing responsible personnel and coordinating with relevant parties to minimize disruptions to the maintenance of equipment and other machinery on the ship. Furthermore, actuating involves efforts to ensure that all human resources work according to their tasks, functions, and competencies in order to achieve company goals. Finally, control is implemented through supervision of each job performed to identify and rectify any potential errors. The results of this study provide insights into the importance of gear pump maintenance and effective strategies in managing the maintenance process. By implementing the appropriate steps, it is expected to enhance the performance of the gear pump, extend its service life, and optimize operational efficiency in the industry.